Factor Model in Cryptocurrency Market (Global Journal of Management and Business Research, 2020)
In our paper, we investigate the explanatory power to the crypto currency return premium of market factor and size factor. We tested both the value-weighted and the equally weighted market factor and a big minus small Fama-French size factor. We found the market and size together can explain 33% of the premium. We also used UMAP to find a non-linear transformation of the crypto returns to create two factors, who can explain over 80% of the premium in both training and testing periods. However, further analysis and research needs to be carried out to decipher what these two factors represent.